The brain takes shape : an early history - Martensen, Robert L. (Robert Lawrence) (Oxford ; New York : Oxford University Press, 2004)
1. Bodies, Words, and Images. 2. Matter, Spirit, and the Heart. 3. The Human Mind and "Gland H": Cartesian Models of Mind, Brain, and Nerves. 4. When the Brain Came Out of the Skull. 5. Toward a New Physiology of Human Conduct. 6. Body of Witnesses. 7. The Transformation of Eve. 8. Mind Without Brain: John Locke, Thomas Syndenham, and the Constitutional Body of the British Enlightenment. 9. On the Persistence of the Cerebral Model and Its Alternatives: A Cultural Anthropology Perspective.
Bodies, words, and images -- Matter, spirit, and the heart -- The human mind and "gland H" : Cartesian models of mind, brain, and nerves -- When the brain came out of the skull -- Body of witnesses -- Toward a new physiology of human conduct -- The transformation of Eve -- Mind without brain : John Locke, Thomas Sydenham, and the constitutional body of the British Enlightenment -- On the persistence of the cerebral body and its alternatives.
Includes bibliographical references and index.
Print version record.
Electronic reproduction.
Master and use copy. Digital master created according to Benchmark for Faithful Digital Reproductions of Monographs and Serials, Version 1. Digital Library Federation, December 2002.
digitized
eBooks on EBSCOhost
Keywords: Medicine -- Philosophy; Human body (Philosophy); Medicine -- History -- 17th century; Philosophy, Medical -- history; History, 17th Century; Philosophy, Medical; Médecine -- Philosophie; Corps humain (Philosophie); Médecine -- Histoire -- 17e siècle.; MEDICAL -- Family & General Practice; MEDICAL -- Osteopathy; MEDICAL; MEDICAL -- Holistic Medicine; HEALTH & FITNESS -- Reference; MEDICAL -- Essays; MEDICAL -- Alternative Medicine; HEALTH & FITNESS -- Holism; Human body (Philosophy); Medicine; Medicine -- Philosophy; Lichaam en geest; Hersenfuncties; Filosofische aspecten; Theologie; Leib-Seele-Problem; Medizin; Philosophie; 1600-1699; Geschichte; Geschichte 1600-1700; History; Electronic books